ANALISIS LAPORAN KEUANGAN TERHADAP PENILAIAN KELAYAKAN PEMBERIAN PEMBIAYAAN PADA CALON NASABAH BANK SYARIAH - Katra Pramadeka; Merta Kusuma (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
This study aims to determine the analysis of the Feasibility Assessment of Giving Prospective Customers of Islamic Bank Financing. The object of this research was carried out in Islamic banks. This research is carried out by using quantitative and qualitative methods, namely analyzing the facts that exist and described in the form of numbers or a way to analyze data by carrying out calculations using financial ratio tools, and comparing a theory that applies to events that occur in the field. The results of the study show that Islamic banks have fulfilled and applied standard principles in providing financing to prospective customers. Based on the results of the application and calculation of financial ratio analysis conducted by Islamic banks. Financial ratio analysis consisting of liquidity ratios, solvency and profitability in good condition and the third number of these ratios in accordance with the standard ratio established by Islamic banks